Application of immunoassay of encephalomyocarditis virus in cell culture with enzyme-labeled virus-specific monoclonal antibodies for rapid detection of virus, neutralizing antibodies, and interferon. - Vlaspolder, F (1988)
Encephalomyocarditis virus (EMCV)-specific monoclonal antibody UM 21.1 labeled with horseradish peroxidase was used to detect EMCV in L-cell monolayers. This direct enzyme immunoassay of EMCV, performed in wells of 96-well plates, could be applied for various purposes, such as early detection of virus multiplication, determination of 50% tissue culture infective doses, and rapid titration of interferon and EMCV-neutralizing antibodies. Multiplication of EMCV is indicated by a rapid increase of the absorbance values measured against EMCV-infected L cells starting as early as 4.5 h after virus inoculation. The early rise of absorbance (i.e., virus multiplication) is inhibited by interferon, allowing its rapid titration. Preincubation of the virus inoculum with neutralizing antibodies also yielded decreased absorbance values. With the latter enzyme immunoassay for neutralizing antibodies, performed after an infection period of 8 h, antibody titers measured were comparable to those obtained with a conventional plaque reduction test. We assume that similar assays could be developed for other picornaviruses (e.g., polioviruses).